Warunki mieszkaniowe robotników na łamach „Gońca Łódzkiego” (1898–1906) - Śmiechowski, Kamil (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
At the turn of the 19th a nd 20th century workers’ living conditions were extremely difficult. The uneasy financial conditions were accompanying overpopulation and bad sanitary conditions of flats. This was a serious social problem. The problem had been widely discussed at the pages of the “Goniec Łódzki”. This daily paper had came out since 1898 till 1906. The paper was often criticizing the housing conditions in Łódź. Usually it shows the examples of cheap houses for workers which had been build at this time in Western Europe, especially in Germany and England. The title was proposing, that such houses ought to be build by philanthropic societies which could assure to their members some limited profits. During the times of the Revolution of 1905 “Goniec” was convincing that the state should also participate in dealing with this problem. Although title’s ideas cannot be realized in poor and undeveloped society, “Goniec” was constantly trying to be a creator of public opinion in the industrial and multicultural Łódź.